2017
DOI: 10.12973/eurasia.2017.00754a
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Mechanism of Entrepreneurial Education Quality, Entrepreneurial Self-efficacy and Entrepreneurial Intention in Social Sciences, Engineering and Science Education

Abstract: Entrepreneurship Education in Colleges and universities is a profound reform of China's higher education paradigm. Which is a necessary choice for Chinese universities to break through the traditional educational model. It is an important measure to cultivate college students' entrepreneurial consciousness, entrepreneurship and entrepreneurial ability. On the whole, entrepreneurship education in China is still in the stage of exploration and rapid development. It is great practical significance and theoretical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 14 publications
2
15
0
2
Order By: Relevance
“…Likewise, a research conducted by Savira(2015)said that self-efficacy and creativity together affect the interest in entrepreneurship. Then, (Jiang, Xiong, & Cao, 2017), in the study entitled the quality of entrepreneurial learning, self-efficacy and entrepreneurial intentions, showed that entrepreneurship learning and self-efficacy jointly influenced the interest in entrepreneurship.…”
Section: The Effect Of Entrepreneurship Learning Self-efficacy and Cmentioning
confidence: 99%
“…Likewise, a research conducted by Savira(2015)said that self-efficacy and creativity together affect the interest in entrepreneurship. Then, (Jiang, Xiong, & Cao, 2017), in the study entitled the quality of entrepreneurial learning, self-efficacy and entrepreneurial intentions, showed that entrepreneurship learning and self-efficacy jointly influenced the interest in entrepreneurship.…”
Section: The Effect Of Entrepreneurship Learning Self-efficacy and Cmentioning
confidence: 99%
“…Mientras que Maresch et al (2016) sí hallaron resultados positivos y significativos, aunque bastante bajos; al igual que Ndofirepi y Rambe (2017), aseverando que la educación emprendedora afectó en los elementos influyentes en la intención emprendedora, pero sin cambios reveladores. En cambio, otros estudios (Hannon, 2006;Jones et al, 2008;Wilson et al, 2009;Lanero et al, 2011;Jiang et al, 2017;Soria-Barreto et al, 2017) encontraron una relación positiva entre educación emprendedora e incremento de las intenciones emprendedoras.…”
Section: Revisión De La Literaturaunclassified
“…Entrepreneurial team is a special team composed of many different individuals, and the diversity of team members may influence strategic decisions of the entrepreneurial team in varying degrees (Khan, 2017;Forsström-Tuominen, Jussila & Goel, 2017). At present, China has preferential policies and encouragement for college students to start their own businesses (Jiang, Xiong & Cao, 2017). However, the research on the entrepreneurial team, especially about the relationship between entrepreneurial team heterogeneity and entrepreneurial decision-making still lacks systematic theoretical and empirical analysis.…”
Section: Y Cao and H Jiang / Research On College Students' Entreprenementioning
confidence: 99%